The Role of Oil Price Fluctuations on the USD/EUR Exchange Rate: An ARDL Bounds Testing Approach to Cointegration - Aimer, Nagmi M. Moftah (Journal of Asian Business Strategy, 2017)
This paper studies the impact of global oil price fluctuations on global exchange rates of the dollar against the euro (USD/EUR), using the bounds testing approach method to test co-integration, error correction model, in the framework of the autoregressive distributed lag (ARDL) by Pesaran et al. (2001) during the period from 1990 to 2016. Moreover, the results of the analysis showed a positive balance relationship between the two variables in the long and short term. On the other hand, our estimates suggest that, 1% depreciation in the dollar leads to 0.58 rises in the oil price in the long run. The error correction results show that coefficient of (ECM) = -0.43, imply that deviation from the long-term exchange rate is corrected by 43% by the following year. Based on the findings of the study, the researcher recommended the need for coordination between movements of oil prices and financial policy for what needs economic political mechanism of delicate balance.